Cardiovascular Toxicity of Targeted Therapies for Cancer: An Overview of Systematic Reviews. Issue 6 (24th August 2020) - Van Leeuwen, Marina T; Luu, Steven; Gurney, Howard; Brown, Martin R; Pearson, Sallie-Anne; Webber, Kate; Hunt, Lee; Hong, Soojung; Delaney, Geoffrey P; Vajdic, Claire M
Abstract: Background: Several targeted therapies for cancer have been associated with cardiovascular toxicity. The evidence for this association has not been synthesized systematically nor has the quality of evidence been considered. We synthesized systematic review evidence of cardiovascular toxicity of individual targeted agents. Methods: We searched MEDLINE, Embase, and the Cochrane Database of Systematic Reviews for systematic reviews with meta-analyses of cardiovascular outcomes for individual agents published to May 2020. We selected reviews according to prespecified eligibility criteria (International Prospective Register of Systematic Reviews CRD42017080014). We classified evidence of cardiovascular toxicity as sufficient, probable, possible, or indeterminate for specific cardiovascular outcomes based on statistical significance, study quality, and size. Results: From 113 systematic reviews, we found at least probable systematic review evidence of cardiovascular toxicity for 18 agents, including high- and all-grade hypertension for bevacizumab, ramucirumab, axitinib, cediranib, pazopanib, sorafenib, sunitinib, vandetanib, aflibercept, abiraterone, and enzalutamide, and all-grade hypertension for nintedanib; high- and all-grade arterial thromboembolism (includes cardiac and/or cerebral events) for bevacizumab and abiraterone, high-grade arterial thromboembolism for trastuzumab, and all-grade arterial thromboembolism for sorafenib and tamoxifen; high- and all-grade venous thromboembolism (VTE) for lenalidomide and thalidomide, high-grade VTE for cetuximab and panitumumab, and all-grade VTE for bevacizumab; high- and all-grade left ventricular ejection fraction decline or congestive heart failure for bevacizumab and trastuzumab, and all-grade left ventricular ejection fraction decline/congestive heart failure for pazopanib and sunitinib; and all-grade corrected QT interval prolongation for vandetanib. Conclusions: Our review provides an accessible summary of the cardiovascular toxicity of targeted therapy to assist clinicians and patients when managing cardiovascular health.